Ancient America - Leonard, Jonathan Norton 1923- (New York Time-Life International, 1968)
Picture and text survey of the cultural and intellectual achievements of American civilizations before Columbus.
The earliest americans -- The great stone cities -- An age of warrior kings -- High culture in the Andes -- Triumphs of native genius -- Horsemen from the sea -- The deathless heritage.
Includes bibliographical references (page 182) and index.
Keywords: Indians -- Antiquities; America -- Antiquities